Neuroendocrine Tumour in a 37-Year-Old Female: A Diagnostic Challenge - Manoj Dongare; Parin Nilesh Patel; Dakshyani Satish Nirhale; Kishore Jeughle; Siddharth Veerla (Journal of Clinical and Diagnostic Research)
Pancreatic Neuroendocrine Tumours (PNETs) are a rare group of neoplasms arising from hormone-producing cells in the pancreas. Unlike the more common pancreatic adenocarcinomas, PNETs often grow more slowly and may produce hormones, leading to distinct clinical symptoms. We present a rare and diagnostically challenging case of a PNET in a 37-year-old female who presented with a three-month history of epigastric pain. Initial imaging studies revealed a mass in the liver, mimicking Hepatocellular Carcinoma (HCC), while subsequent investigations, including Positron Emission Tomography-Computed Tomography (PET-CT) and ultrasound-guided Fine-Needle Aspiration Cytology (FNAC), suggested a PNET. A Whipple procedure was performed, and histopathological examination confirmed the diagnosis. This case highlights the importance of a multidisciplinary approach in managing rare and challenging malignancies, emphasising the need for clinical vigilance, advanced imaging, and histopathological evaluation to confirm the diagnosis. The successful management of this case underscores the critical role of timely surgical intervention and personalised treatment strategies in achieving favourable outcomes.